Respostas
respondido por:
2
Resposta:
Explicação passo-a-passo:
a
[ (1/2)³ * ( 1/2)^-2 ]/ [( 1/2)^-6 ]
NUMERADOR
( 1/2)^3 + (-2) OU ( 1/2)^3 -2 = ( 1/2)¹ >>>> NUMERADOR
( 1/2)¹: ( 1/2)^-6 = ( 1/2)^1-(-6) = ( 1/2)^1+6 = ( 1/2)^7 >>>> RESPOSTA
B
(10² * 8³ )/ ( 1/2)^-6
NUMERADOR
10² * 8³ = 100 * 512 = 51200 >>>NUMERADOR
( 1/2)^-6 = (2/1)^6 = 64 DENOMINADOR
INVERTE A BASE E PASSA EXPOENTE PARA MAIS
51 200/ 64 = 800 >>>> RESPOSTA
Perguntas similares
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás